Glass Beads, Markers of Ancient Trade in Sub-Saharan Africa: Methodology, State of the Art and Perspectives - (:unkn) unknown (My University, 2019)
Glass beads have been produced and traded for millennia all over the world for use as everyday items of adornment, ceremonial costumes or objects of barter. The preservation of glass beads is good and large hoards have been found in archaeological sites across the world. The variety of shape, size and colour as well as the composition and production technologies of glass beads led to the motivation to use them as markers of exchange pathways covering the Indian Ocean, Africa, Asia, Middle East, the Mediterranean world, Europe and America and also as chronological milestones. This review addresses the history of glass production, the methodology of identification (morphology, colour, elemental composition, glass nanostructure, colouring and opacifying agents and secondary phases) by means of laboratory based instruments (LA-ICP-MS, SEM-EDS, XRF, NAA, Raman microspectroscopy) as well as the mobile instruments (pXRF, Raman) used to study glass beads excavated from sub-Saharan African sites. Attention is paid to the problems neglected such as the heterogeneity of glass (recycled and locally reprocessed glass). The review addresses the potential information that could be extracted using advanced portable methods of analysis.
Keywords: African Research